Organ-Specific Toxicities Due to Radiation Therapy in Cancer Patients With or Without HIV Infection: A Systematic Review of the Literature - Xu, Melody J.; Liewen, Alison; Valle, Luca; Olson, Adam C.; Zetola, Nicola M.; Grover, Surbhi (Frontiers in Oncology, 2018)
BACKGROUND: To synthesize published literature on the association between human immunodeficiency virus (HIV) infection and radiation therapy (RT)-related toxicities. METHODS: Two electronic databases, MEDLINE and Embase, were searched to identify studies published before November 2016 comparing RT-related toxicities between HIV-infected and HIV-uninfected patients receiving RT or chemoradiation therapy (CRT) for cancer. A qualitative synthesis of included articles and organ-specific toxicities was then performed. RESULTS: Of the 21 studies included in this review, 15 reported on anal cancer treatment, three on cervical cancer, two on Kaposi sarcoma, and one on prostate cancer. Reports in the pre-antiretroviral therapy (ART) or early ART era tended to identify increased morbidity and mortality with HIV infection. However, modern series incorporating more concurrent chemotherapy, conformal RT techniques, and ART administration result in fewer studies reporting toxicity differences in patients treated for anal and cervical cancers. When statistically significant, HIV-infected patients had higher rates of gastrointestinal toxicity with anal cancer CRT (up to 50%) and higher rates of hematologic toxicity with cervical cancer CRT (up to 31%). Of the 17 studies reporting treatment outcomes, nine suggest HIV-infected patients may have reduced local control and/or survival rates. CONCLUSIONS: Overall, RT is likely similarly tolerated between HIV-infected and HIV-uninfected patients, especially with modern RT techniques. HIV-infected patients should continue to receive established standard of care RT and CRT dosing.